2020
DOI: 10.3389/fmars.2020.592255
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Diversity Effect on Ecosystem Functioning in a Coastal Upwelling System

Abstract: Species composition plays a key role in ecosystem functioning. Theoretical, experimental and field studies show positive effects of biodiversity on ecosystem processes. However, this link can differ between taxonomic and functional diversity components and also across trophic levels. These relationships have been hardly studied in planktonic communities of coastal upwelling systems. Using a 28-year time series of phytoplankton and zooplankton assemblages, we examined the effects of phytoplankton diversity on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 80 publications
(110 reference statements)
1
16
1
Order By: Relevance
“…The importance of top-down control mechanisms revealed in this study contradicts with many studies that emphasize the impacts of bottom-up control mechanisms (e.g., Scherber et al, 2010;Hertzog et al, 2016;Otero et al, 2020). One possible explanation to this disagreement is the fact that our data come from an aquatic system, whereas the majority studies demonstrating bottom-up control mechanisms is conducted in terrestrial systems (as reviewed in Haddad et al, 2009).…”
Section: Discussioncontrasting
confidence: 92%
“…The importance of top-down control mechanisms revealed in this study contradicts with many studies that emphasize the impacts of bottom-up control mechanisms (e.g., Scherber et al, 2010;Hertzog et al, 2016;Otero et al, 2020). One possible explanation to this disagreement is the fact that our data come from an aquatic system, whereas the majority studies demonstrating bottom-up control mechanisms is conducted in terrestrial systems (as reviewed in Haddad et al, 2009).…”
Section: Discussioncontrasting
confidence: 92%
“…Its progressive dominance therefore impacted competitors and constrained productivity as indicated by the increase in selection effects and reduction in complementarity effects over time, which is expected in stable environments (Hodapp et al., 2016). Natural phytoplankton assemblages show similar positive selection effects where the identity and traits of dominant species affect BEF relationships (Hodapp et al., 2015; Otero et al., 2020). Nonetheless, biodiversity effects were up to five times stronger in communities than pairs.…”
Section: Discussionmentioning
confidence: 93%
“…The results demonstrated that larger phytoplankton taxa were in equilibrium and dominance phenomenalike those occurring during bloom events when opportunistic species (i.e., diatoms) tend to dominate over other phytoplankton taxa-were not observed. As evenness (distribution of taxa) responds more quickly than richness (number of taxa) to variation in the environmental conditions [31], this suggests that the MMW were in a "transition phase".…”
Section: Role Of the Straits As A Biodiversity Mixermentioning
confidence: 99%
“…It is well known that phytoplankton diversity and community structure influence the functioning of ecosystems [29,30]. However, more information is needed to improve knowledge on relations between phytoplankton diversity and upwelling ecosystem functioning [31].…”
Section: Introductionmentioning
confidence: 99%